Health education as practice of nurses in family health strategy - Oliveira, Mariana de Brito; Cavalcante, Edilma Gomes Rocha; Oliveira, Dayanne Rakelly de; Leite, Cícero Emanoel Alves; Machado, Maria de Fátima Antero Sousa (Rev Rene, 2013)
Descriptive, exploratory study, with a qualitative approach, which aimed at identifying knowledge and practice of health education of nurses from the Family Health Strategy, in November and December, 2009. The interviews, conducted with fifteen nurses in Crato, Ceará, Brazil, were subjected to content analysis. Four categories were identified: Conception on health education, Action planning, working in partnerships; limits and capability in implementing educational actions. The conceptions of health education still reflect a conservative view, but the practice was positive because it prioritizes several topics, using local resources and venues and involving other sectors. The difficulties were related to excessive assignments, interaction with certain groups and discontinuity of actions. There is the need for better coordination and organization of the health service in the pursuit of partnerships with emphasis on interdisciplinary and intersectoral activities aimed at health promotion.DOI:https://doi.org/10.15253/2175-6783.2013000500005